Oral health knowledge, attitude and practices among university staff and relations to socio-demographic and employment characteristics in 2020 - Omayma, Kirouani (2021)
Oral health is a look of well-being that needs to be considered, and its absence predisposes oral diseases, which cause tooth damage, pain, reduced work productivity, and thus a reduced quality of life. Staff’s knowledge, attitudes, and practices are essential for good oral health. The aim of this study is to evaluate oral health-related knowledge, attitude, and practices and determine their association with socio-demographic factors and employment factors among Universiti Putra Malaysia (UPM) staff. A descriptive cross-sectional study involving 207 staff (academic and non-academic) was used. Stratified random sampling was used to select a representative sample with selected faculties (Faculty of Environmental Studies, Engineering, Agriculture, Medicine and Health Sciences, Modern Language, and Communication). Oral health knowledge, attitude, and practices were assessed with a validated and pretested questionnaire. Data collected via online e-mail were analyzed using the Statistical Package of Social Sciences (SPSS)version 25. Data analysis was conducted in three stages: univariate, bivariate, and multivariate analysis. The total respondents were 162 from 207 subjects (sample size of the study), giving a response rate of 78.3%. In this study, more than half of the participants have satisfactory knowledge (56.2%), a positive attitude (66%), and correct practices (53.7%). Despite this remains a significant proportion of staff, who have insufficient knowledge and incorrect practices. The Chi-square tests show a significant association between oral health knowledge and level of education, monthly income, faculty, type of staff, and smoking. Besides that, oral health practice is associated with monthly income and years of experience. This suggests initiating of oral health awareness program for the staff members to promote their knowledge, attitude, and practices in oral health.